Microperimetric changes and fixation stability status after half-dose photodynamic therapy for chronic central serous chorioretinopathy - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2020)
Purpose: The aim of this study was to evaluate the effect of half-dose verteporfin photodynamic therapy on central retinal sensitivity, status of fixation stability, and choroidal thickness in patients with chronic central serous chorioretinopathy. Methods: In total, 22 eyes of 22 patients with chronic central serous chorioretinopathy were enrolled, and all the eyes received indocyanine green angiography-guided half-dose verteporfin photodynamic therapy. Best-corrected visual acuity, contrast sensitivity, and retinal sensitivity in the central 10 degrees and status of the fixation stability are assessed by MAIA microperimetry, and optical coherence tomography findings (central macular thickness and subfoveal choroidal thickness) were evaluated at baseline and 1, 3, and 6 months after the half-dose verteporfin photodynamic therapy. Results: Subretinal fluid was completely resolved in 9 eyes at 1 month and in 17 eyes at 3 months. There was recurrence in two eyes at 6 months and five of the eyes had a persistent subretinal fluid through all the time points. Best-corrected visual acuity, contrast sensitivity, and retinal sensitivity improved significantly 6 months after half-dose verteporfin photodynamic therapy. Fixation stability did not change in either follow-up visit. Central macular thickness and subfoveal choroidal thickness decreased significantly at 6 months of the visits compared to baseline. There was not any systemic and ocular side effect after the treatment. Conclusion: This study shows that there is significant improvement in best-corrected visual acuity, contrast sensitivity, and retinal sensitivity after half-dose verteporfin photodynamic therapy. The status of fixation stability remained unchanged in the eyes with chronic central serous chorioretinopathy after half-dose verteporfin photodynamic therapy. Furthermore, half-dose verteporfin photodynamic therapy is also effective in decreasing central macular thickness and subfoveal choroidal thickness.
Keywords: Central serous chorioretinopathy; fixation stability; microperimetry; half-dose verteporfin photodynamic therapy; CHOROIDAL THICKNESS; MACULAR DEGENERATION; FLUENCE; EYES; VERTEPORFIN; SENSITIVITY